Terfenadone is a strong inhibitor of CYP2J2 present in the human liver and intestinal microsomes. Issue 3 (June 2018) - Lee, Eunyoung; Kim, Ju-Hyun; Shon, Jong Cheol; Wu, Zhexue; Kim, Hyun Ji; Gim, Minsik; Lee, Taeho; Liu, Kwang-Hyeon
Abstract: Cytochrome P450 2J2 (CYP2J2) is involved in the metabolism of drugs, including albendazole, astemizole, ebastine, and endogenous substrates. In a previous study, we used recombinant CYP2J2 and determined whether danazol, hydroxyebastine, telmisartan, and terfenadone inhibited CYP2J2 by using four representative CYP2J2 substrates, namely albendazole, astemizole, ebastine, and terfenadine. In this study, we evaluated the inhibitory potential of these four chemicals on human liver and intestinal microsomes, which are commonly used in a reaction phenotyping study. Among the four CYP2J2 inhibitors tested, terfenadone was strongest inhibitor of CYP2J2-mediated metabolism of albendazole, astemizole, and terfenadine with IC50 values of 0.31, 0.15, and 2.11 μM, respectively, in human liver microsomes (HLMs). In addition, terfenadone had strong inhibitory effect on the metabolism of the abovementioned drugs in human intestinal microsomes (HIMs), with IC50 values of 0.43, 0.08 and 1.07 μM, respectively. Danazol, weakly inhibited CYP2J2-mediated metabolism of albendazole and astemizole with IC50 values of 13.8 and 18.3 μM, respectively in HLMs, whereas it strongly inhibited the CYP2J2-mediated ebastine hydroxylase activity in HLMs and HIMs (IC50  = 1.93–1.95 μM). Our data suggest that terfenadone may be used as a general CYP2J2 inhibitor in reaction phenotyping study using HLMs and HIMs regardless of the substrate used. Graphical abstract: